PERSEPSI MASYARAKAT DAN WISATAWAN DALAM PENGEMBANGAN EKOWISATA AIR TERJUN KELAMBU DI DESA BUKIT TINGGI KECAMATAN GUNUNGSARI - Wulandari, Ni Wayan Maika Putri; Wahyuningsih, Endah; Anwar, Hairil (Jurusan Kehutanan, 2022)
Ecotourism is a broad part of ecotourism that includes the supporting sector of tourism activities. To support environmental conservation efforts and increase community participation in the management or development of ecotourism so as to provide economic benefits to the community and local government. community perceptions affect the development of ecotourism. This study aims to determine the perception of the community and visitors around the area towards the development of the ecotourism of Kelambu Waterfall and to know the strategy of developing Kelambu Waterfall ecotourism in Bukit Tinggi Village. The method used is observation, interviews, and questionnaires. Data analysis used descriptive qualitative analysis and SWOT analysis. The results showed that the public perception of the Kelambu Waterfall tourism object as a whole obtained a total of 140 with a fairly high category, where the highest point was in the fifth point about public perception of the need for socialization about tourism to improve human resources with a total score of 23.88. Tourist perceptions of ecotourism development as a whole are obtained with a score of 169 with a fairly high category, and strategies in overcoming the weaknesses and threats that arise to the development of Waterfall tourism objects are carried out by means of promotion or marketing of destinations and bias monitoring through social media that very developed in modern times and coordinate with the government to work together, in the development of tourism objects.